Assessment of Chinese medicine for coronavirus-related pneumonia: A protocol for systematic review and meta-analysis. Issue 24 (12th June 2020) - Zhu, Yibing; Jiang, Zhiming; Zhang, Yuke; Zhang, Qi; Li, Wen; Ren, Chao; Yao, Renqi; Feng, Jingzhi; Ren, Yu; Jin, Lin; Wang, Yang; Du, Bin; et al.
Abstract: Background: The 2019 novel coronavirus disease has caused a global pandemic with substantial morbidity and mortality. Chinese medicine has been extensively employed in the coronavirus-related pandemic in China. We aim to assess the efficacy and safety of Chinese medicine in treatment of coronavirus-related pneumonia with the updated results of relevant clinical trials. Methods: Six electronic databases including PubMed, EMBASE, Cochrane Library, China National Knowledge Infrastructure, Chongqing VIP, and SinoMed will be searched to identify randomized controlled trials up to May 2020. Patients diagnosed with coronavirus-related pneumonia including severe acute respiratory syndrome, Middle East respiratory syndrome, and 2019 novel coronavirus disease and administrated with Chinese medicine will be included. The primary outcome is the all cause mortality at the longest follow up available. The second outcomes include the length of stay in hospital and intensive care units, the duration of mechanical ventilation, and adverse events. The pooled effects will be analyzed and reported as risk ratios for dichotomous data using the Mantel–Haenszel method or mean differences for continuous data using the inverse-variance method. Sensitivity and subgroup analyses will be performed to test the robustness of the results and to explore the potential sources of heterogeneities. The Egger test and/or funnel plots will be used for the examination of publication bias. The grades of recommendation assessment, development, and evaluation methodology will be used to summarize the quality of evidence. The trial sequential analysis will be conducted to test whether the meta-analysis has a sufficient sample size after adjustment of the increased type I and II error risks. Results: The evidence to date of Chinese medicine in treatment of coronavirus-related pneumonia will be systematically reviewed and meta-analyzed. Conclusion: The relevant studies will be summarized and further evidence will be provided. PROSPERO registration number: CRD42020178879